The economic burden of breast cancer in western Iran: a cross-sectional cost-of-illness study - Banafsheh Darvishi Teli; Meysam Behzadifar; Mania Beiranvand; Aziz Rezapour; Seyed Jafar Ehsanzadeh; Samad Azari; Ahad Bakhtiari; Payam Haghighatfard; Mariano Martini; Maryam Saran; Masoud Behzadifar (Journal of Health, Population and Nutrition)
Abstract Background Breast cancer is a significant global health challenge, affecting millions annually and imposing a considerable burden on healthcare systems and economies worldwide. This cross-sectional study aims to determine the economic impact of breast cancer in Lorestan Province, western Iran. Methods A retrospective cost-of-illness analysis utilizing a cross-sectional design was performed from November 2023 to July 2024. Data were collected using patient medical records and telephonic interviews. Costs were categorized into direct medical costs, direct non-medical costs, and indirect costs. A bottom-up approach was employed for cost calculation from a societal viewpoint, with a prevalence-based analysis. Results The study analyzed 525 patients with an average age of 42.74 ± 11.75 years. The total economic burden of breast cancer was estimated at $5,394,409.13, with a mean of $10,275.07 per patient. Direct medical costs comprised 70.2% of the total expenses, primarily attributed to hospitalization, chemotherapy, and laboratory tests. Direct non-medical costs, including accommodation and transportation for patients and their companions, accounted for 12.5%. Indirect costs, largely stemming from productivity losses due to morbidity and mortality, represented 17.3% of the total burden. Conclusion Breast cancer imposes a substantial economic burden on patients and their families in Lorestan Province. Enhancing health insurance coverage, providing government subsidies for treatment, and improving healthcare infrastructure to offer advanced diagnostic and treatment options locally are critical steps to alleviate this burden. Early detection and prevention programs can facilitate earlier diagnosis and reduce treatment costs. Comprehensive policies addressing both medical and non-medical expenses are necessary to improve patients’ quality of life and lessen the financial challenges associated with breast cancer in Iran.